On the Impact of Uncertain Cost Reduction When Selling to Strategic Customers - Shum, Stephen; Tong, Shilu; Xiao, Tingting (Management Science, 2017)
Many products undergo cost reductions over their product life cycles. However, strategic customers may have more incentive to wait if they expect a cost reduction to lead to a price drop. A firm that does not face any uncertainty can use pricing strategies such as price commitment and price matching to alleviate the strategic waiting of customers. However, these pricing strategies provide less flexibility than dynamic pricing for a firm facing uncertainty. In this paper, we examine the impact of cost reduction under dynamic pricing, price commitment, and price matching when cost reduction can come from production learning or from technology advancement. The firm makes pricing decisions when facing uncertainty in future cost, and strategic customers decide whether to wait when facing uncertainty in future price. We show that in general the firm’s profit is higher when future cost is more uncertain, but not necessarily when cost reduction is more significant. In addition, production learning and technology advancement can have opposite effects on the optimal pricing decisions and the choice of pricing strategy. This paper was accepted by Yossi Aviv, operations management.